DIGITAL SKILLS FOR EDUCATORS AND PARENTS IN THE CONTEXT OF HIGH - QUALITY EDUCATION - Prudnikova, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The purpose of the research is to identify commonalities and possible differences in the assessment of educators’ and parents’ attitudes towards digital technologies, reasons for their usage, and identify motivation to improve their digital skills. The study is built on research activities and there are used both theoretical and empirical methods. Quantitative methods in the form of questionnaires are used during the study. The researcher is more important to identify precedents and learn about the character of educators’ and parents’ attitudes. Dinamic environment for teaching should be supported by positive attitude to tehnologies. The statistical programme used for the analyses and presentation of data in this research is the Statistical Package for the Social Sciences (SPSS). In conclusion: the results from this study will be used to support interesting directions for future research in the context of higt –quility education.